Los conflictos del documental español: el caso de Basilio Martín Patino - Manuel de la Fuente (Cahiers de Civilisation Espagnole Contemporaine)
Spanish filmmaker Basilio Martín Patino’s documentaries show a number of textual and political issues and conflicts. The aim of this paper is to study the following features in three particular films (Canciones para después de una guerra, Madrid y Libre te quiero): fiction vs. nonfiction narrative; the political depiction of the city of Madrid; and the tools of censorship in different contexts. Martín Patino’s discourse has been critical with mainstream industries and narratives throughout his career and thus has been sidelined within the different cultural systems both in dictatorships and democratic regimes.